If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -3(3x + -4) = 30 Reorder the terms: 6x + -3(-4 + 3x) = 30 6x + (-4 * -3 + 3x * -3) = 30 6x + (12 + -9x) = 30 Reorder the terms: 12 + 6x + -9x = 30 Combine like terms: 6x + -9x = -3x 12 + -3x = 30 Solving 12 + -3x = 30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -3x = 30 + -12 Combine like terms: 12 + -12 = 0 0 + -3x = 30 + -12 -3x = 30 + -12 Combine like terms: 30 + -12 = 18 -3x = 18 Divide each side by '-3'. x = -6 Simplifying x = -6
| -16+13=m-5 | | 3z+46=1+8z | | 1+1/5p=-7 | | 7x+4(-2x-5)=-31 | | -30n=-27n-57 | | -30n=-27n-57 | | 7b^2-32b-60=0 | | 6x+7-5x=13 | | 2-6p=8 | | 18.9125-(1/4) | | f(0)=-7x^2+9x+7 | | (3x-1)/4=(5x+3)/6 | | 5x+3(-7x-4)=116 | | 5i/3-9i | | 1/5(2x-4)=7 | | 15x-10(1/15+10/15x)=1 | | 4x-12=2x+30 | | -4y(8x)= | | 3g+5=7g+3 | | 6x-5=7x+6 | | 7a=33-4a | | (x+5)/3=(3x-6)/2 | | 1/3x-2/5=0 | | 1/4(7y-1)+1/8(2y+7) | | 6x^2-2xy+7y^2-2=0 | | (2x+1)/3=(4x-7)/5 | | 8x=3x-55 | | 7x+7(-2x-6)=-112 | | -2(r+6)=-39 | | 2x-4=-4x | | 4m-(-2)=18 | | 9p^2=24p-16 |